Eksklusi Sosial dalam Pendidikan: Analisis Komparatif Indonesia dan Vietnam - Al-Faiza, Ananda Putri Aqila; Fitri, Nur Lailatul; Tsany, Abyan; Aqilah, Aidah Farah (Pustaka Peradaban, 2025)
This study analyzes social exclusion in education in Indonesia and Vietnam, evaluates existing policies, and proposes policy recommendations to enhance educational inclusion. Using a systematic literature review method, data were collected from various academic sources, reports from international organizations, and government policy documents. The analysis was conducted using a thematic approach based on the theories of Somerville, Byrne, and MacMullin. The findings indicate that social exclusion in education in both countries is influenced by economic and geographical factors, as well as ethnic and gender-based discrimination. Although Vietnam has adopted more structured inclusive policies, challenges to ensuring educational access for marginalized groups persist. In Indonesia, policy implementation continues to face obstacles regarding equitable access and effectiveness at the local level. This study recommends strengthening affirmative policies, improving educational infrastructure in remote areas, and actively involving communities in education policy formulation. These findings are expected to serve as a reference for policymakers in designing more inclusive strategies to reduce social exclusion in education Penelitian ini menganalisis eksklusi sosial dalam pendidikan di Indonesia dan Vietnam, mengevaluasi kebijakan yang telah diterapkan, serta memberikan rekomendasi kebijakan untuk meningkatkan inklusi pendidikan. Menggunakan metode studi literatur sistematis, data dikumpulkan dari berbagai sumber akademik, laporan organisasi internasional serta dokumen kebijakan pemerintah. Analisis dilakukan dengan pendekatan tematik berdasarkan teori Somerville, Byrne, dan MacMullin. Hasil penelitian menunjukkan bahwa eksklusi sosial dalam pendidikan di kedua negara dipengaruhi oleh faktor ekonomi, geografis, serta diskriminasi berbasis etnis dan gender. Meskipun Vietnam telah mengadopsi kebijakan inklusif yang lebih terstruktur, tantangan dalam akses pendidikan bagi kelompok marjinal masih terjadi. Di Indonesia, implementasi kebijakan masih menghadapi kendala dalam pemerataan akses dan efektivitas di tingkat lokal. Penelitian ini merekomendasikan penguatan kebijakan afirmatif, peningkatan infrastruktur pendidikan di daerah terpencil, serta keterlibatan aktif komunitas dalam perumusan kebijakan pendidikan. Temuan ini diharapkan dapat menjadi referensi bagi pembuat kebijakan dalam merancang strategi yang lebih inklusif untuk mengurangi eksklusi sosial dalam pendidikan.